Influenza and pertussis vaccination of women during pregnancy in Victoria, 2015–2017. Issue 10 (21st April 2019) - Rowe, Stacey L; Perrett, Kirsten P; Morey, Rosemary; Stephens, Nicola; Cowie, Benjamin C; Nolan, Terry M; Leder, Karin; Pitcher, Helen; Sutton, Brett; Cheng, Allen C
Abstract: Objectives: To assess variations by time of year and hospital in the uptake of influenza and pertussis vaccinations by pregnant women in Victoria; to identify factors associated with vaccination uptake. Design, setting: Retrospective analysis of data in the Victorian Perinatal Data Collection (VPDC), a population surveillance system for obstetric conditions, procedures, and pregnancy and birth outcomes. Participants: Women whose pregnancies ended in a live or stillbirth during July 2015 – June 2017. Main outcome measures: Influenza and pertussis vaccinations during pregnancy. Results: 153 980 pregnancies in 67 hospitals ended during July 2015 – June 2017; 59 968 pregnant women (39.0%) were vaccinated against influenza and 98 583 (64.0%) against pertussis. Coverage varied by pregnancy end date, rising for influenza during winter and spring, but for pertussis rising continuously across the two years from 37.5% to 82.2%. Differences between hospitals in coverage were marked. Factors associated with vaccination included greater maternal age, primigravidity, early antenatal care, and GP‐led care. The odds of vaccination were statistically significantly lower for women born overseas and those who smoked during pregnancy; the odds of vaccination were also lower for Aboriginal and Torres Strait Islander women. Conclusions: Pertussis vaccination of pregnant women in Victoria has increased, but influenza vaccination rates remain moderate and variable. Structural changes at the system level may improve maternal vaccination rates. Embedding the delivery of maternal vaccination programs in antenatal care pathways should be a priority.